Pengaruh Model Flipped Classroom Terhadap Self Efficacy Siswa Pada Pembelajaran Tatap Muka Terbatas - Yulistina Nur DS; Ayu Fitri; Tia Latifatusadiah; Sinta Maria Dewi; Fajar Febriansyah (Jurnal Penelitian Pendidikan IPA, 2023)
Learning can run well and achieve the desired goals if students feel comfortable and not pressured and have high self-efficacy. Learning activities in Indonesia at the beginning of the COVID-19 pandemic had to be carried out through online or online distance learning, which had an influence on students' self-efficacy. During the research, MI Ar Rahmah, Bengle Village, Majalaya District, Karawang Regency, did not fully offline or face-to-face learning at school, so learning used offline and online methods. The learning model that can be applied in situations like this is the flipped classroom model. In learning using the flipped classroom learning model, it is expected that there will be an influence on students' self-efficacy. This study was conducted to prove whether or not there are differences in the self-efficacy of students who use the flipped classroom model and those who do not use the flipped classroom model in limited face-to-face learning at MI Ar Rahmah, Bengle Village, Majalaya District, Karawang Regency